INOVASI DALAM PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDES) KEMBANG KENANGA DESA PISANG BEREBUS KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI TAHUN 2020 - Rendi Riandika; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
One of the efforts made by the village government, especially in improving the welfare and economy of the community, is by establishing a Village-Owned Enterprise (BUMDes), based on Law Number 6 of 2014 concerning Villages Article 87. Pisang Berebus Village is one of the villages that has BUMDes in Gunung Toar District, where the BUMDes has not run optimally since it was inaugurated in 2020. This study aims to determine innovation in the development of BUMDes Kembang Kenanga Desa Pisang Berboil in 2020 and find out the inhibiting factors for innovation in the development of BUMDes Kembang Kenanga Desa Pisang Berboil in 2020. The theory used in this study is the theory of innovation according to Muluk namely product innovation, process, service methods, policy strategies and systems. The research approach used is a qualitative approach and descriptive research type. Data were collected by the authors using interview and documentation techniques. The data used are primary data obtained from research informants and further supported by secondary data obtained from various government agencies related to this research. The results of the research show that innovation in developing BUMDes Kembang Kenanga Desa Pisang Berebus in 2020 is not optimal. The implementation of innovations carried out by both the Village Government and BUMDes Management has not gone well. The innovation carried out is optimizing the presence of BUMDes by prioritizing and focusing on one trading business unit. Innovation in BUMDes development has not been maximized in terms of product innovation, process innovation, service method innovation, strategy or policy innovation and system innovation. The inhibiting factors are: capital constraints because in 2020 there is Covid-19, limited human resources due to inadequate facilities and infrastructure and low mastery of managerial skills because it is not easy for villages to find someone who has superior capabilities in managing and developing BUMDes businesses. Keywords: Innovation, Village, Development of BUMDes